2002
DOI: 10.1007/s00454-002-2801-9
|View full text |Cite
|
Sign up to set email alerts
|

A Cube Tiling of Dimension Eight with No Facesharing

Abstract: A cube tiling of eight-dimensional space in which no pair of cubes share a complete common seven-dimensional face is constructed. Together with a result of Perron, this shows that the first dimension in which such a tiling can exist is seven or eight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…The last case was discovered by Lagarias and Shor [67], and the other cases were consequences of Mackey [73]. In general we have ξ n+1 ≤ ξ n + 1.…”
Section: Theorem 73 (Lagarias and Shormentioning
confidence: 84%
“…The last case was discovered by Lagarias and Shor [67], and the other cases were consequences of Mackey [73]. In general we have ξ n+1 ≤ ξ n + 1.…”
Section: Theorem 73 (Lagarias and Shormentioning
confidence: 84%
“…The conjecture was proved to be true for n ≤ 6 in [Pe40]. It was proved to be false for n ≥ 10 in [LaSh92] and for n ≥ 8 in [McKa02]. The counterexample found were of class T 2 .…”
mentioning
confidence: 93%
“…The higher the dimension of the space, the more freedom we get. Keller's conjecture for the remaining dimensions was solved in 2002 by M a c k e y [16], who showed that the conjecture is false for n = 8, 9 as well, and finally this year M y r v o l d et al (private communication) showed, providing a computer based proof, that Keller's conjecture is true for n = 7.…”
Section: Introductionmentioning
confidence: 99%